POTENSI KUPU-KUPU SEBAGAI DAYA TARIK EKOWISATA DI KAWASAN JATILUWIH, BALI - Anak Agung Gde Raka Dalem (Fakultas Pariwisata Universitas Pancasila, 2021)
Research on “Butterflies potentials as ecotourist attractions in Jatiluwih area, Bali” was undertaken in 2018. Objectives on this research were: to discover species of butterflies found in Jatiluwih area, as well as to find out their potentials as ecotourist attractions. Samples were collected through exploration of the research sites and though interview. Butterflies caught on sites brought to the laboratorium at Udayana University for their species identification. Results of observation was identified by using hand books such as Bland and Jaques (1978), Landman (2001), Lilies S. (1992), Mason (2005), etc. The data of butterflies recorded such as the species and its relative numbers/freqwency, status (protected/not protected), etc. The potential of butterflies as ecotourist attractions such as analysed though the availability of attractions, especially the richness of butterfly species in Jatiluwih. In addition, location where butterflies have been packed into tourist or ecotourist attractions, as well as how to make the package (if available) would be reported. Results of this research showed that 33 species of butterflies have been identifies in Jatiluwih area, in which one of those is protected by law. Jatiluwih has a potential in development of butterflies as ecotourist attractions. This could be seen from richness of butterflies species sighted in Jatiluwih as well as the existence of rare or protected species. Accesibility to Jatiluwih was also well, accommodation were available predominantly in the form of homestays, food stalls/restaurantswere also available here, as well as from the existence of support from policy issued by the government in the development of tourism. To the research conducted (2018), there was no use of butterflies as a special ecotourist product attractions here. Keywords: butterflies, eco-tourism, Jatiluwih area, Bali